Assay and physicochemical characterization of the antiparasitic albendazole - Noely Camila Tavares Cavalcanti; Giovana Damasceno Sousa; Maria Alice Maciel Tabosa; José Lamartine Soares Sobrinho; Leila Bastos Leal; Davi Pereira de Santana (Universidade de São Paulo, 2012)
The aim of this study was to characterize three batches of albendazole by pharmacopeial and complementary analytical techniques in order to establish more detailed specifications for the development of pharmaceutical forms. The ABZ01, ABZ02, and ABZ03 batches had melting points of 208 ºC, 208 ºC, and 209 ºC, respectively. X-ray diffraction revealed that all three batches showed crystalline behavior and the absence of polymorphism. Scanning electron microscopy showed that all the samples were crystals of different sizes with a strong tendency to aggregate. The samples were insoluble in water (5.07, 4.27, and 4.52 mg mL-1, respectively) and very slightly soluble in 0.1 M HCl (55.10, 56.90, and 61.70 mg mL-1, respectively) and additionally showed purities within the range specified by the Brazilian Pharmacopoeia 5th edition (F. Bras. V; 98% to 102%). The pharmacopeial assay method was not reproducible and some changes were necessary. The method was validated and showed to be selective, specific, linear, robust, precise, and accurate. From this characterization, we concluded that pharmacopeial techniques alone are not able to detect subtle differences in active pharmaceutical ingredients; therefore, the use of other complementary techniques is required to ensure strict quality control in the pharmaceutical industry. O objetivo do trabalho foi caracterizar três lotes de albendazol com técnicas analíticas farmacopéicas e complementares a fim de estabelecer especificações mais detalhadas para o desenvolvimento de formas farmacêuticas. Os lotes ABZ01, ABZ02 e ABZ03 apresentaram fusão em 208 ºC, 208 ºC e 209 ºC. Foi possível evidenciar, por difração de raios X, que os três lotes apresentaram comportamento cristalino e ausência de polimorfismo. Através da microscopia eletrônica de varredura verificou-se que todas as amostras apresentaram cristais com diferentes tamanhos e forte tendência de agregação. As amostras foram insolúveis em água (5,07; 4,27 e 4,52 µg mL-1) e muito pouco solúveis em HCl 0,1M (55,10; 56,90 e 61,70 µg mL-1) e, ainda, apresentaram pureza dentro da faixa especificada pela F.Bras.V (98% a 102%). O método farmacopéico de doseamento não foi reprodutível, e algumas mudanças foram necessárias. O método foi validado e demonstrou ser seletivo, específico, linear, robusto, preciso e exato. A partir dessa caracterização, pode-se concluir que apenas técnicas farmacopéicas não são capazes de detectar diferenças sutis entre os ingredientes farmacêuticos ativos, necessitando, portanto, de uso de outras técnicas complementares para garantir um rígido controle de qualidade na indústria farmacêutica.